2020
DOI: 10.15419/psc.v7i1.407
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of cancer stem-like cells from hepatocellular carcinoma cell line HepG2 by methods of magnetic-activated cell sorting, spheroid culture, and anti-tumor drug-resistant selection: A primary evaluation

Abstract: Introduction:Recently reported data have suggested that only a small subset of cancer cells possess the capability to initiate malignancies. These observations were based on investigation of cells within the primary tumors displaying a distinct surface marker pattern. CD133 marker is a putative hematopoietic and neuronal stem cell marker, which is also considered to be a tumorigenic marker in brain, prostate and liver. Recent studies have shown that a small population of CD133-positive cells, indeed, exists in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
1
1
0
Order By: Relevance
“…Figure 1C reveals that HepG2 cells with the shape of neurons are resistant to cisplatin. This result agrees with a previous study that detected chemoresistant HepG2 cells with the shape of neurons which are positive for a neuronal stem marker CD133 [24]. Western blot analyses with β-III-tubulin and NeuN confirmed that the cells resistant to cisplatin treatments are positive for markers of neurons (Figure 1D).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Figure 1C reveals that HepG2 cells with the shape of neurons are resistant to cisplatin. This result agrees with a previous study that detected chemoresistant HepG2 cells with the shape of neurons which are positive for a neuronal stem marker CD133 [24]. Western blot analyses with β-III-tubulin and NeuN confirmed that the cells resistant to cisplatin treatments are positive for markers of neurons (Figure 1D).…”
Section: Resultssupporting
confidence: 92%
“…The inhibition of DNA replication by anti-cancer drug gemcitabine parallels the inhibition of CAFs and blocks the formation of tumor clusters in cells derived from lung metastases. Gemcitabine is an FDA-approved inhibitor of DNA replication and effectively kills cancer cells by increasing apoptosis [24][25][26]. We found that in a low-density setting, LM81 cells treated with gemcitabine (5 nM) do not form tumor clusters, compared to DMSO-treated cells (Figure 9A).…”
Section: Resultsmentioning
confidence: 92%